Soil organic matter from southern pine biofuel feedstocks under different soil types and management systems - Mosier, Samantha, author; Paustian, Keith, author; Davies, Christian, author; Cotrufo, M. Francesca, author (Colorado State University. Libraries, 2017)
Using pre-commercial thinnings in pine plantations has the potential to deliver sustainable biofuels. However, the removal of biomass from these plantations could reduce C inputs belowground and overall C storage. This study analyzes soil C and N stocks to estimate stock changes, as a function of soil type and different management systems. Soil cores were taken from 12 different southern pine plantations, representing 4 different soil types. Each site had 2 silvicultural regimes across 3 levels of pre-commercial thinning. Soils were separated into meaningful fractions to understand how much soil organic matter is bioavailable and how much is stabilized.
198 - Samantha Mosier